Assédio moral em universidades federais do rio grande do sul: identificação e estratégias de coibição Santana do Livramento – RS - Jacobus, Betania Severo (2025)
The study aims to analyze the strategies that three Federal Universities in the state of Rio Grande do Sul promote to curb bullying within them. The universities considered for this study are UFSM, UNIPAMPA, and UFRGS. Therefore, a content analysis of reports on the universities' websites was conducted. This is a case study with a qualitative, descriptive approach, conducted from January to May 2025. The data collection technique used was documentary research. The choice to study universities as public institutions was based on the book "Discomfort at Work – Redefining Moral Harassment" by Marie-France Hirigoyen. The book describes that bullying is more prevalent in the public sector than in the private sector and that education is one of the most affected by bullying practices. Therefore, we decided to study how some of the largest Federal Universities in Rio Grande do Sul address the issue of bullying and what effective measures they adopt to combat and prevent bullying. The results revealed that these universities implement some deterrent strategies. UFRGS has a support center within the university, as well as a research center that seeks to disseminate research results and support victims. UFSM has a manual that outlines ways to prevent bullying. It emphasizes the participation of institutional staff in university decisions. UFSM reiterates that bullying practices should be reported to the Ombudsman's Office, which has the necessary authority to issue sanctions. UNIPAMPA, on the other hand, develops booklets, promotes online lectures, and places posters in university bathrooms and hallways. However, I believe these actions could be more aggressive